An Optical Overview of Poly[𝝁𝟐-L-alanine-𝝁𝟑-nitrato-sodium(I)] Crystals - E. Gallegos-Loya; E. Orrantia-Borunda; A. Duarte-Moller (The Scientific World Journal)
Single crystals of the semiorganic materials, L-alanine sodium nitrate (LASN) and D-alanine sodium nitrate (DASN), were grown from an aqueous solution by slow-evaporation technique. X-ray diffraction (XRD) studies were carried for the doped grown crystals. The absorption of these grown crystals was analyzed using UV-Vis-NIR studies, and it was found that these crystals possess minimum absorption from 200 to 1100 nm. An infrared (FTIR) spectrum of single crystal has been measured in the 4000–400 cm-1 range. The assignment of the observed vibrational modes to corresponding symmetry type has been performed. A thermogravimetric study was carried out to determine the thermal properties of the grown crystal. The efficiency of second harmonic generation was obtained by a variant of the Kurtz-Perry method.